2020
DOI: 10.1101/2020.11.08.371922
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TSC1loss-of-function increases risk for tauopathy by inducing tau acetylation and preventing autophagy-mediated tau clearance

Abstract: Age-associated neurodegenerative disorders demonstrating tau-laden intracellular inclusions, including Alzheimer’s disease (AD), frontotemporal lobar degeneration (FTLD) and progressive supranuclear palsy (PSP), are collectively known as tauopathies. The vast majority of human tauopathies accumulate non-mutant tau rather than mutant forms of the protein, yet cell and animal models for non-mutant tauopathies are lacking. We previously linked a monoallelic mutation in the TSC1 gene to tau accumulation and FTLD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 82 publications
(135 reference statements)
0
1
0
Order By: Relevance
“…Eukaryotic translation initiation factor 4E-binding protein 1 (EIF4EBP1) functions as a translation repressor protein, and phosphorylated EIF4EBP1 levels have been reported to be significantly increased in AD brains compared to controls [35], while increased levels have been found in the CSF and plasma of AD patients [36]. Interestingly, tuberous sclerosis protein 1 (TSC1) has been genetically linked with AD, while loss of TSC1 is associated with tauopathy in in vitro and in vivo studies [37,38]. Protein Phosphatase 2 Regulatory Subunit B'Delta (PPP2R5D) has also been associated with tau hyperphosphorylation [39,40] and studies have reported decreased PPP2R5D expression and activity in the AD hippocampus [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Eukaryotic translation initiation factor 4E-binding protein 1 (EIF4EBP1) functions as a translation repressor protein, and phosphorylated EIF4EBP1 levels have been reported to be significantly increased in AD brains compared to controls [35], while increased levels have been found in the CSF and plasma of AD patients [36]. Interestingly, tuberous sclerosis protein 1 (TSC1) has been genetically linked with AD, while loss of TSC1 is associated with tauopathy in in vitro and in vivo studies [37,38]. Protein Phosphatase 2 Regulatory Subunit B'Delta (PPP2R5D) has also been associated with tau hyperphosphorylation [39,40] and studies have reported decreased PPP2R5D expression and activity in the AD hippocampus [41,42].…”
Section: Discussionmentioning
confidence: 99%